Mjuua agapanthi gen. et sp. nov., a biotrophic mycoparasite of Fusarium spp. - Crous, P.W.; Dijksterhuis, J.; Figge, M.; Sandoval-Denis, M. (Westerdijk Fungal Biodiversity Institute, 2024)
Fusarium agapanthi is newly reported from the centre of origin of Agapanthus in South Africa, where it is associated with dead flower stalks of Agapanthus praecox.Mjuua agapanthi, a rare hyphomycete with a morphology corresponding to asexual morphs of Pyxidiophora, was isolated as mycoparasitic on F. agapanthi, along with bacteria that co-occurred in synnematal heads of M. agapanthi. Germinating conidia of M. agapanthi were observed to parasitise germinating conidia of F. agapanthi. Although M. agapanthi could not be cultivated on its own, the association with Fusarium proved to not be restricted to F. agapanthi, as it could also be cultivated with other Fusarium spp. Mjuua agapanthi is a member of Pyxidiophorales, an order of obligate insect parasitic microfungi. The exact role of the bacteria in synnematal heads of M. agapanthi remains to be further elucidated, although one bacterium, Alsobacter metallidurans, appeared to cause lysis of the synnematal conidial cell walls. This discovery suggests that many unculturable obligate biotrophic microbes can probably be cultivated if co-cultivated with their respective hosts.